Malachite Green Dye Removal Using the Seaweed Enteromorpha - R. Jayaraj; M. Chandra Mohan; P. Martin Deva Prasath; T. Hidhayathullah Khan (E-Journal of Chemistry)
Malachite green adsorption from an aqueous solution onto activated Enteromorpha carbon has been studied experimentally using batch adsorption method. Adsorption kinetics and equilibrium were investigated as a function of initial dye concentration, pH, contact time and adsorbent dosage. Kinetics studies indicated that the adsorption followed pseudo second order reaction. Equilibrium data was analyzed using Langmuir and Freundlich isotherm models. The adsorption capacity of Enteromorpha was found to be 94.74%. On the basis of experimental results and the model parameters, it can be inferred that the carbonaceous Enteromorpha is effective for the removal of malachite green from aqueous solution.